(untitled) (Saptagandaki Journal, 2025)
Environmental concerns and unsustainable consumption have increased the importance of green marketing and sustainable consumption practices. Although prior studies have examined consumer attitudes toward green products, limited attention has been paid to brand related factors influencing attitudes toward branded green products, particularly in developing countries. This study examines the influence of green price sensitivity and green brand knowledge (brand image, brand awareness, and brand quality) on consumers’ attitudes toward branded green products in Nepal. Using a cross-sectional survey design, data were collected from 388 green product users through purposive sampling, and multiple regression analysis was applied. The results show that green brand image and green brand quality significantly and positively influence attitudes toward branded green products, while green price sensitivity has a significant negative effect. However, general attitudes toward green products and green brand awareness do not significantly contribute to brand attitude formation. The findings suggest that Nepalese consumers distinguish between generic green products and branded green offerings, emphasizing quality and brand image over environmental awareness alone. The study contributes to green marketing literature by highlighting the critical role of brand specific factors and offers practical insights for marketers aiming to promote responsible consumption.